Psychosocial risks and the job activity of banking sector employees - Aleksander Stańczak; Agnieszka Mościcka-Teske; Dorota Merecz-Kot (Nofer Institute of Occupational Medicine, 2014)
Background: Psychosocial risks, via stress mechanism, may negatively influence employees' health and work activity. Both the scale and the type of these risks depend on job specificity in particular occupation or sector. The aim of the study was to characterize the categories of stressors occurring in the banking sector and their effects on employees' performance. Material and Methods: The studied subjects were 484 employees tested with the questionnaire method. The Scale of Psychosocial Risk was used as a research tool. Results: The more the employees are exposed to threats connected with work content, work context, pathologies and specific factor, the less satisfied they are and the more frequently they declare turnover intention. However, rarely does it change their engagement or absence. The subjects felt the effects of risks, regardless of their stressfulness. It turns out that individual's well-being is rather related to work context, e.g. relations with co-workers or salary, than to the character of tasks. It was observed, that with age, employees are less resistant to work context related to threats, which results in frequent absence. Conclusions: Most of the results comply with the literature data. The work environment diagnosis may be based only on the occurrence of psychosocial risks, regardless of the subjectively experienced stress. The conclusions can be used by both employers and specialists in occupational stress prevention. Med Pr 2014;65(4):507-519